Isolamento reprodutivo e reciprocidade em espécies simpátricas de Chamaecrista Moench. (Fabaceae) - BEZERRA, Thatiany Teixeira (2019)
Knowledge of interspecific reproductive strategies allows us to formulate hypotheses about the events that lead to the existence and maintenance of natural barriers. Studies related to the existence of hybrids in Chamaecrista. We aim to investigate how barriers of reproductive isolation among the sympatric species of: C. ramosa; C. rotundifolia; C. rotundifolia var. rotundifolia; C. hispidula and C. flexuosa. The study was conducted at the RPPN of Nossa Senhora do Oiteiro de Maracaípe, Ipojuca-PE. In the 1st chapter The possible barriers of reproductive isolation were investigated through: 1) Observation of the distribution in the space of the natural borders; 2) monitoring the flowering period; 3) description of the enantiosthetic types (morphological barrier) and 4) interspecific two-way crosses (physiological barrier); and 5) pollinator-sharing research (ecological barrier). This spices were observed synchronoptric, which have in common the overlapping the distribution of the wagon of the weddings and the period of floration. All crosses were fruits, with the exception of C. flexuosa x C. rotundifolia var. rotundifolia. The success in the most expressive pollination treatments was 80% for C. rotundifolia x C. rotundifolia var. rotundifolia, in contrast, low formation between C. flexuosa x C. hispidula, C. flexuosa x C. ramosa (5%) each. In the crosses in contact with C. flexuosa and C. ramosa the high fruit volume (89.5-95%) was observed, around 5 to 10 days after a pollination. Seed germination was the viability of the species C. ramosa and C. hispidula (G = 8-24%). The maximum germination macroscopies occur for C. rotundifolia var. rotundifolia x C. hispidula (G = 100%) and C. hispidula x C. rotundifolia var. rotundifolia (G = 83.3%). Bees of the genus Florilegus sp. visit flowers of the Ramosa type, suggesting the potential for continuous hybridization. All floral cases were bees, with C. ramosa receiving a greater diversity of visitors (n = 8). Xylocopa carbonaria, X. cearense and Eufrisea sp. share C. flexuosa and C. ramosa flowers. Eufrisea sp. present in all studied Chamaecrista species, except for C. rotundifolia. An analysis of the enantiosthetic types pointed out three different: Ramosa, Flexuosa, Amiciella. That, its functionality demonstrate greater efficiency as barrier of isolation, since the present indicates reduction in the pre and post reproductive success. For this chapter, we investigated the possibility of reciprocity deviations between species and the same area of study mentioned above, relating to the reproductive system and the variables of adaptive response of the natural forces in relation to the reciprocal hercogamic pattern. We aimed the intra and interspecific reciprocity in enantiostyl flowers of C. ramosa and C. rotundifolia. Through a bank of images of flowers of the species, with scale in millimeters. The images were collected in 10 open flowers of the day for 10 (C. ramosa, n = 100) and five (C. rotundifolia; n = 50) days in three groups per species. They were analyzed in a grid tray (letters x numbers) and with the aid of the power point software, in addition to making the floral flowering, besides the floral floral of the stigma and the faltal petal. We verified that interspersed days there is production of flowers of larger sizes. For Chamaecrista ramosa the floral morphology varied between 20.7-24.3mm and C. rotundifolia ranged from 7.7-12.6mm in length. C. ramosa presents a larger floral size and a greater amplitude of uptake and deposition of pollen compared to C. rotundifolia, being thus able to present as a promoter of increase of the area of deposition and capture of pollutant pollen, increasing the specificity of the crosses and reduction as chances of geitonogamy.